Citra Makanan Indonesia dalam Puisi di Atas Meja Makan: Kajian Gastrokritik - Icha Nurhalimah; Ari Ambarwati (JENTERA: Jurnal Kajian Sastra, 2023)
This study focuses on describing the image of Indonesian food in the collection of Poems on the Dining Table by Nova. In general, poetry only introduces how the author feels about what he feels about life, but through this gastrocritical research researchers want to show the distinctive form of poems with food themes and as a form of characteristics and culture from the area. Gastronomy has an important role to play in conveying the history of food it originated and became more than just food. The methods used in this study are qualitative methods and careful reading methods to describe the concept of gastrocriticism in culinary and art. The procedures in data collection used to collect data are the stage of determining the source of the data, the stage of reading the whole, the stage of categorizing the concept of gastrocriticism, and the stage of describing the results of gastrocriticism. The discovery of culinary and artistic concepts in poetry on the dinner table includes, 1) the image of taste, 2) the way of presentation, and 3) the way the food is consumed. Of the three culinary and artistic concepts, the most dominant result obtained in poetry research on the dinner table is the way of presentation. AbstrakPenelitian ini berfokus untuk mendeskripsikan citra makanan Indonesia dalam kumpulan Puisi di Atas Meja Makan karya Nova. Pada umumnya puisi hanya mengenalkan bagaimana perasaan penulis terkait apa yang dirasakan tentang kehidupan, tetapi melalui penelitian gastrokritik ini peneliti ingin menunjukan bentuk khas dari puisi-puisi yang bertema makanan dan sebagai bentuk ciri khas dan budaya dari daerah tersebut. Gastronomi memiliki peran penting dalam menyampaiakan sebuah sejarah makanan itu berasal dan menjadi lebih dari sekedar makanan. Metode  yang digunakan dalam penelitian ini berupa metode kualitatif dan metode membaca cermat untuk mendeskripsikan konsep gastrokritik pada kuliner dan seni. Prosedur dalam pengumpulan data yang digunakan untuk mengumpulkan data yaitu tahap menentukan sumber data, tahap membaca keseluruhan, tahap mengkategorikan konsep gastrokritik, dan  tahap menjabarkan hasil dari gastrokritik. Penemuan konsep kuliner dan seni dalam puisi di atas meja makan diantaranya, 1) citra rasa, 2) cara penyajian, dan 3) cara makanan tersebut dikonsumsi. Dari ketiga konsep kuliner dan seni, hasil yang diperoleh dalam penelitian puisi di atas meja makan yang paling dominan adalah Citra rasa.